COVID-19 Presentation in Association with Myasthenia Gravis: A Case Report and Review of the Literature - Aksoy, Elif (Case Rep Infect Dis, 2020)
Currently, there are scarce data on how COVID-19 affects people with myasthenia gravis. Theoretically, there is a higher risk of experiencing severe manifestations of COVID-19 due to the common use of immunosuppressive drugs and potential respiratory failure in relation to respiratory muscle weakness. This is one of the early cases of COVID-19 reported in association with myasthenia gravis. Here, we highlight the prognosis, discuss the pathophysiological mechanisms, and prompt the consideration of convalescent plasma therapy in myasthenia gravis patients with concomitant COVID-19.